Punishment System for Narcotics Crime Perpetrators: Case Study: Drug Trafficking in Medan Marelan - Juliandi Juliandi; Jessica Evi Margaretha; Dina Pratiwi Tambun; Parlaungan Gabriel Siahaan; Dewi Pika Lumban Batu (Edumaspul: Jurnal Pendidikan, 2023)
This research was conducted to find out what the criminal system is for drug trafficking and used a case study of drug trafficking in Marelan, Medan based on the judge's decision at the Medan District Court. Drug trafficking is a form of violation of the law in criminal law regulated in Law no. 35 of 2009 concerning drugs. North Sumatra is one of the largest contributors to drug trafficking in Indonesia, specifically in the city of Medan. North Sumatra is one of the largest contributors to drug trafficking in Indonesia, specifically in the city of Medan. The government, narcotics department and other law enforcers must be able to collaborate with the community to thoroughly investigate drug trafficking cases. This research uses descriptive qualitative research methods and interviews with the judge who handled this case. In this research, chronological results were found up to the judge's decision and the punishment system for drug dealers. This research focuses on drug trafficking cases and the criminal system and judge's decisions in handling drug trafficking cases